Effect of cementation protocols on the fracture load of bilayer ceramic crowns manufactured by the Rapid Layer Technology - da Silva, Sarah Emille Gomes (2024)
To evaluate the fracture load of bilayer ceramic crowns manufactured by Rapid Layer Technology (RLT) after different cementation protocols of the veneering ceramic to the zirconia infrastructures. Sixty epoxy resin preparations simulating a molar tooth were obtained and 60 zirconia infrastructures and feldspathic crowns were manufactured by RLT and divided into 6 groups according to the cementation protocol at the interface to veneering ceramic (n=10): Ctr-control: conventional resin cement; Al-Al2O3 sandblasting 50µm + conventional resin cement; Al/MDP-Al2O3 sandblasting (50µm) + resin cement with MDP; Sil-silicatization 30µm + conventional resin cement; Gl/HF-glaze + hydrofluoridric acid (5%,60s) + silane + conventional resin cement; Gl-glazing as bonding agent. The feldspathic ceramic internal surface was etched with fluoridric acid (5%) + silane followed by cementation according to respective protocols. All samples were mechanically cycled (200N and 4.5x105 Pa, 37°C, 2x106 cycles, 3.4Hz) and submitted to axial compressing fracture load test (10kN, 0.5mm/min). The results(N) were submitted to descriptive and analytical statistical analysis with 1-way ANOVA, Weibull, and the Tukey test (α=0.05). ANOVA revealed that there was a significant difference among the tested groups (p<0.0001). The group Al/MDP presented the higher resistance to fracture (1972.46A N), followed by the Ctr group (1584.41B N). The characteristic strength(σ0) was significantly different (p=0.000). The crack and chipping were the predominant failures. The air-abrasion at the external surface of zirconia with Al2O3 followed by cementation with MDP resin cement, should be selected to Rapid Layer Technique when felspathic ceramic is used as veneer ceramic.